LIVING ACCORDING WITH REASON: ABOUT THE STOIC DEFINITIONS OF TELOS (Disertaciones, 2015)
According to the fragments of Stoicism, each principal formulated his own definition of telos. This paper aims to make an interpretation of the definition which reads live harmoniously, awarded to the founder, Zeno of Citium. Also, accordingly to the way his succesors Cleanthes of Assos and Chrysippus of Soli interpreted the predicate with nature it was added to the original formula. The analysis is built on three Stoics concepts: logos, Nature and oikeiosis. We try to show that the definition of the successors develops the founder’s teachings, without contradicting the original doctrine. Which is why the three definitions of the telos refer to the same thing: the attainment of the end of human life and happiness lies in the rationality of the world, of which humans are only its glint.
Keywords: oikeiosis; physis; rationality; telos